Immune Therapy in Pancreatic Cancer: Now and the Future? - Zhang, Yue; Choi, Minsig (Reviews on Recent Clinical Trials, 2015)
Pancreatic cancer continues to be the most lethal malignancy with rising incidence. Traditional chemotherapy remains the standard treatment for advanced pancreatic cancer. Regimens like FOLFIRINOX (5-FU, leucovorin, irinotecan, and oxaliplatin) or gemcitabine and nab-paclitaxel have been used to palliate symptoms and prolong survival. Immune therapy is changing the current treatment paradigm for malignancy, especially with the recent development of antibodies that can modulate immune checkpoint pathways. Immunotherapy to treat pancreatic cancer is a promising approach due to its low toxicity and potential for creating life- long immune response. Multiple large phase III trials using simple vaccination strategies have failed to modulate the immune response in pancreatic cancer. However novel strategies with whole cell vaccines using hyperacute rejections (Algenpantucel- L) immunotherapy demonstrated 62% and 86% 12-month disease free survival and overall survival in resected pancreatic cancer patients. Combination of whole cell vaccine GVAX and mesothelin-secreting vaccine CRS-207 demonstrated an overall survival benefit in metastatic refractory pancreatic cancer patients. In the paper, we review the recently published and ongoing clinical trials using immune based treatment for pancreatic cancer.
Keywords: Check point inhibitors